Microstructure and Reciprocating Sliding Wear Resistance of a Heat-Treated Alloyed Nodular Cast Iron - Ayadi, Souad; Boulifa, Mohammed Iliasse; Kaleli, Emrullah Hakan (SPRINGER LONDON LTD, 2026)
In this study, the effect of alloying elements and heat treatment on the microstructure and reciprocating sliding wear resistance of nodular cast iron was investigated. The studied ductile cast iron was produced in an industrial environment and alloyed with carbide-forming elements (Ti, Nb, V and Mo) in addition to Ni. After austenitization at 900 degrees C for 120 min followed by oil quenching and tempering at 380 degrees C for 90 min, the microstructure evolved from a ferritic matrix containing nodular graphite and MC-type carbides to a dual-phase matrix composed of martensite and retained austenite with graphite nodules and finely dispersed precipitates. This microstructural transformation increased the hardness from 260 HB in the as-cast conditions to 294 HB after heat treatment. Under oil-lubricated reciprocating sliding conditions at 100 degrees C, the coefficient of friction decreased from 0.1136 to 0.1012, corresponding to a reduction of 10.87%, while the wear rate decreased significantly from 11.58 & times; 10 & sup3; & micro;m & sup3;/N.m to 0.85 & times; 10 & sup3; & micro;m & sup3;/N.m, representing a reduction of 92.64%. Surface analyses confirmed the improved wear behavior and reduced surface degradation after heat treatment. The enhanced tribological performance is mainly attributed to the synergistic effect of the dual-phase matrix and the uniformly distributed fine precipitates, which increase the matrix strength and improve the resistance to plastic deformation and material removal. The obtained results highlight the effectiveness of the developed multi-alloyed heat-treated nodular cast iron in improving the tribological performance under lubricated operating conditions, making it a promising material for demanding engineering applications.
Keywords: Nodular cast iron; Alloying elements; Heat treatment; Microstructure; Reciprocating sliding wear; TRIBOLOGICAL BEHAVIOR; DUCTILE IRON; Automation & Control Systems; Engineering